2007
DOI: 10.1002/pmic.200700626
|View full text |Cite
|
Sign up to set email alerts
|

Role of group A Streptococcus HtrA in the maturation of SpeB protease

Abstract: The serine protease high-temperature requirement A (HtrA) (DegP) of the human pathogen Streptococcus pyogenes (group A Streptococcus; GAS) is localized to the ExPortal secretory microdomain and is reportedly essential for the maturation of cysteine protease streptococcal pyrogenic exotoxin B (SpeB). Here, we utilize HSC5 (M5 serotype) and the in-frame isogenic mutant HSC5DeltahtrA to determine whether HtrA contributes to the maturation of other GAS virulence determinants. Mutanolysin cell wall extracts and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Due to its human health importance, the emm1 epidemic clone has been extensively studied by many investigators (25)(26)(27)(28)(29)(30). The identification of polymorphisms in several genes that confer a SpeB-deficient phenotype has led, in part, to the hypothesis that epidemic emm1 GAS strains are under intense selective pressure to decrease secreted SpeB protease activity during infection (19)(20)(21)(22)(23)(24). Reinforcing this idea, Kansal et al, using a small sample of strains, reported an inverse relationship between SpeB proteolytic activity and disease severity (23).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Due to its human health importance, the emm1 epidemic clone has been extensively studied by many investigators (25)(26)(27)(28)(29)(30). The identification of polymorphisms in several genes that confer a SpeB-deficient phenotype has led, in part, to the hypothesis that epidemic emm1 GAS strains are under intense selective pressure to decrease secreted SpeB protease activity during infection (19)(20)(21)(22)(23)(24). Reinforcing this idea, Kansal et al, using a small sample of strains, reported an inverse relationship between SpeB proteolytic activity and disease severity (23).…”
Section: Discussionmentioning
confidence: 71%
“…Each stage is regulated by multiple GAS accessory factors (Table 1). Disruption of any of these components may render a GAS strain deficient in secreted SpeB protease activity (19)(20)(21)(22)(23)(24)). …”
mentioning
confidence: 99%
“…HtrA is a bifunctional enzyme with both chaperone and protease activities and it is thought to be involved in the folding and maturation of secreted proteins as well as in the degradation of proteins that misfold during secretion (22,30,64,81,94,102), and at least in Bacillus subtilis, htrA is induced by secretion stress (2,44,63). Deletion of htrA conferred only a marginal sensitization to the arylomycin and did not significantly affect stationary-phase protein secretion in the presence or absence of the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Highly complex protein samples can be separated according to their pI and their molecular weight using 2-DE [11][12][13][14][15]. The separated proteins can subsequently be visualized using standard protein stains (e.g., Coomasssie blue and silver staining).…”
Section: Detection Of Phosphoproteinsmentioning
confidence: 99%
“…Since ETD and ECD are optimal methods for fragmentation of multiply charged peptide ions (e.g., charges of 13,14), an alternative protease might be a better choice as trypsin mainly produces doubly charged ions, which are suitable for CID. Lys-C is a logical choice as it generates trypsin-like peptide ions, but only cleaves C-terminal to lysine, thus creating longer peptides.…”
Section: Electron Transfer Dissociationmentioning
confidence: 99%